2009
DOI: 10.1136/jme.2008.027383
|View full text |Cite
|
Sign up to set email alerts
|

Split views among parents regarding children’s right to decide about participation in research: a questionnaire survey

Abstract: Based on extensive questionnaire data, this paper focuses on parents' views about children's right to decide about participation in research. The data originates from 4000 families participating in a longitudinal prospective screening as 1997. Although current regulations and recommendations underline that children should have influence over their participation, many parents in this study disagree. Most (66%) were positive providing information to the child about relevant aspects of the study. However, respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…There is considerable discontinuity and variability in the psychological development of pediatric populations, particularly in cognitive, socio-emotional, and neurological development which makes it implausible to establish a single age-based standard for when to defer to the judgments of pediatric research participants (Kon 2006; Masty and Fisher 2008; see Spears 2010 for excellent review of adolescent neurological capacities). Moreover, the standards for a valid assent may change over the course of longitudinal studies because of changes in an adolescent’s development (Helgesson 2005; Swartling et al 2009). …”
Section: The State Of the Art Of Assent To Pediatric Researchmentioning
confidence: 99%
“…There is considerable discontinuity and variability in the psychological development of pediatric populations, particularly in cognitive, socio-emotional, and neurological development which makes it implausible to establish a single age-based standard for when to defer to the judgments of pediatric research participants (Kon 2006; Masty and Fisher 2008; see Spears 2010 for excellent review of adolescent neurological capacities). Moreover, the standards for a valid assent may change over the course of longitudinal studies because of changes in an adolescent’s development (Helgesson 2005; Swartling et al 2009). …”
Section: The State Of the Art Of Assent To Pediatric Researchmentioning
confidence: 99%
“…A survey of 7-to 14-year-olds who were enrolled in clinical research or receiving clinical care for cancer or asthma reported that approximately 90% of young people felt that they should be involved in decisions, whereas only approximately 60% of parents agreed. 84 Just over 40% of parents were against or unsure about whether children should have decisional authority over participation in non-therapeutic clinical research, 100 while nearly 70% of parents responding to a hypothetical research scenario said that they would impose their own views on research participation regardless of their child's wishes. 102 Particularly where the child has a life-threatening illness, some parents report excluding the child from the decisions about research altogether in order to protect them from distressing information, or including their child in discussions but making the trial decision themselves.…”
Section: Young People's Role In the Trial Decisionmentioning
confidence: 99%
“…Some researchers have argued that while young people's dissent should be respected, they are not in a position to make a decision on trial entry without significant guidance from their parents, 97,98 and that, while it is important that they are consulted, they should be protected from decisions that they are unwilling, or unable, to make. 99 A key complexity in considering research in this area is that much of it has investigated young people's decision-making about entry into hypothetical trials or non-therapeutic clinical research, 87,[100][101][102][103][104][105] rather than focusing on young people who have been approached about a 'real' clinical trial. Moreover, some research in this area has been conducted with samples of healthy children, rather than children who have recent experience of illness.…”
Section: Young People's Role In the Trial Decisionmentioning
confidence: 99%
“…By that time a majority of the children were 12-13 years old, an age that required positive assent by the children (Gustafsson Stolt et al, 2005;Swartling et al, 2009). …”
Section: The Abis Studymentioning
confidence: 99%